Conservation planning of vertebrate diversity in a Mediterranean agricultural-dominant landscape - de la Montaña, Enrique; Rey Benayas, José M.; Vasques, Ana; Razola, Irene; Cayuela, Luis (Biological Conservation, 2011)
To improve effectiveness of protected areas, selection of priority areas should include consideration of three main components, namely special conservation elements, focal species and representation. We present a three-track approach related to these components for vertebrate conservation planning in Castilla-La Mancha, central Spain. As special conservation elements, we identiﬁed Priority Areas for Conservation of species using ﬁve criteria: species richness, geographic rarity, species vulnerability, a Combined Index of these three criteria, and a Standardised Biodiversity Index (SBI) that integrate the three criteria and four studied taxa. The Natura 2000 Network was used to include conservation areas for focal species. We evaluated the representation of every landscape type in the existing conservation areas. To delineate the spatial conﬁguration for vertebrate conservation, we combined the identiﬁed Priority Areas for Conservation, existing conservation areas and connectivity areas by cost–distance analysis. The Combined Index was the most efﬁcient criterion analyzed to identify Priority Areas for Conservation. The Natura 2000 Network showed a high percentage of coincidence with identiﬁed Priority Areas for Conservation, whereas the natural protected areas network had a low percentage of coincidence. Six agricultural landscapes were inadequately represented in the current conservation network. According to our multitrack approach, 29% of study area was required to capture 100% of vertebrate species and all landscape types. Our results show that the existing conservation areas are insufﬁcient to guarantee the conservation of biodiversity in the study region. Additional areas with outstanding features of diversity, connectivity areas, and establishment of targets for off-reserve conservation are of fundamental importance for strengthening biodiversity conservation.
Keywords: Agroecosystem; Combined Index of biodiversity; Gap analysis; Landscape representation; Least-cost path analysis; Natura 2000 Network

Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment - Cayuela, Luis; Rey Benayas, Jose Maria; Maestre, Fernando T; Escudero, Adrián (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ecological stability; Initial floristic composition; Vegetation dynamics; Woody vegetation cover

Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment - Cayuela, Luis; Rey Benayas, Jose Maria; Maestre, Fernando T.; Escudero, Adrián (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75015 PARIS, FRANCE publisher: GAUTHIER-VILLARS/EDITIONS ELSEVIER
Keywords: Ecological stability; Initial floristic composition; Vegetation dynamics; Woody vegetation cover